PERAN WAKAF, INFAQ, DAN SEDEKAH DALAM PEMBANGUNAN PONDOK PESANTREN (STUDI KASUS PONDOK PESANTREN DARUL MUZAKKI) - Ardianita Thresnasari; Nur Diana; Harun Al Rasyid (El-Aswaq, 2022)
Through the management and development of ziswaf as support in the management of existing developmentfacilities in Islamic boarding schools as a support for Islamic boarding school activities, which producephysical objects that are material. In the development process, planning for each stage has the ability to supportdevelopment for the next stage. The purpose of this study was to determine the management and role of waqf,infaq, and alms in the construction of Darul Muzakki Islamic Boarding School. Using content analysis methodsto get conclusions. Primary data obtained through interviews and documentation. The results of this studyindicate that waqf management is carried out by individual nadzir and waqf has a role to be used as land forinfrastructure development of Darul Muzakki Islamic Boarding School. The management of infaq and alms usestraditional methods that do not meet the existing development accountability procedures, but infaq and alms actas operational funds that can produce physical objects. The existence of development can have a positive impacton students so that they can have a proper place to study